A unique complement derived chemotactic factor for tumor cells. - Romualdez, A G (1975)
A factor chemotactic for Walker carcinosarcoma and Novikoff hepatoma tumor cells can be generated by incubation of serum with an extract from tumor cells. The chemotactic factor has no activity for neutrophilic leukocytes, and three factors chemotactic for leukocytes are not chemotactic for tumor cells. By the use of complement deficient serums as well as purified complement components, the chemotactic factor for tumor cells has been found to be a fragment of the fifth component (C5) of complement and appears to result from direct interaction of C5 with an enzyme in the extract. The chemotactic factor for tumor cells can be classified as a functionally unique fragment of C5 that may significantly influence the behavior of tumor cells in vivo.